‘Sontoloyo' and 'Genderuwo'; Critical Discourse Analysis on Jokowi’s Utterance - Nanan Abdul Manan (Institut Agama Islam Negeri (IAIN) Kendari, 2019)
This study discusses Joko Widodo’s utterance in several moments. Jokowi is the president of the Indonesian Republic. He would like to participate in the reelection of the presidential election in April 2019. Many statements of him make public perceptions appear different. In this case, there is two big points of research that can be famous dictions in this era. ‘sontoloyo’ and ‘genderuwo’ are two interesting dictions to discuss. As a popular person, Jokowi’s utterances occur as public discourses. Many perspectives are produced by many analysts in multidiscipline views. Critical Discourse Analysis (CDA) is used as a framework to analyze the utterances related to many perspectives of language. Fairclough model is a choice for analyzing in depth of the research. It states in three big points; text analysis (description), processing analysis (interpretation) andsocial analysis (explanation). The researcher uses a qualitative method. The data related with the sontoloyo and genderuwo utterance comes from news online the Jakarta Post. By using Fairclough theory, the researcher explains the text in the relationship with the situation of political moment, the speaker as government and candidate of the presidential election. The text gives many interpretation and relationship with the social condition.